PENDAMPINGAN SERTIFIKASI HALAL UNTUK PELAKU USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI DESA CIMALAKA KECAMATAN CIMALAKA KABUPATEN SUMEDANG - Muharram Fauzi, Yasir; Aprilia, Erika (Jurnal Abdimas Bina Bangsa, 2025)
Many people experience halal certification of food and beverage products from Micro, Small and Medium Enterprises (MSMEs). This incident is caused by several factors such as minimal literacy of halal certification, guarantee of halalness of a product, and requirements for making halal certificates that are not followed. This problem does not get a solution because there is no mentoring process from certified human resources who accompany MSMEs. People tend to be apathetic to process halal certification applications because they are hampered by minimal literacy, regulations that do not want to be processed, and ignoring the urgency of halal certification. Therefore, halal certification mentoring activities are needed for MSMEs. The method of activity carried out is by means of preliminary studies and document studies. Furthermore, observations are made to MSMEs. Then seminars are held, questions and answers, and halal certification is processed starting from the creation of a Business Identification Number, Taxpayer Identification Number, and a halal account in the online system. The result is that MSMEs who have not received halal certificates receive halal certificates.